Ethical and social issues in the information age - Kizza, Joseph Migga (Texts in Computer Science, 2013)
The rapid pace of change in computing demands a continuous review of our defensive strategies, and a strong ethical framework in our computer science education. This fully revised and enhanced fifth edition of Ethical and Social Issues in the Information Age examines the ethical, social, and policy challenges stemming from the convergence of computing and telecommunication, and the proliferation of mobile information-enabling devices. This accessible and engaging text surveys thought-provoking questions about the impact of these new technologies. Topics and features: Establishes a philosophical framework and analytical tools for discussing moral theories and problems in ethical relativism Offers pertinent discussions on privacy, surveillance, employee monitoring, biometrics, civil liberties, harassment, the digital divide, and discrimination Examines the new ethical, cultural and economic realities of computer social network ecosystems (NEW) Reviews issues of property rights, responsibility and accountability relating to information technology and software Discusses how virtualization technology informs our ethical behavior (NEW) Introduces the new frontiers of ethics: virtual reality, artificial intelligence, and the Internet Surveys the social, moral and ethical value systems in mobile telecommunications (NEW) Explores the evolution of electronic crime, network security, and computer forensics Provides exercises, objectives, and issues for discussion with every chapter This comprehensive textbook incorporates the latest requirements for computer science curricula. Both students and practitioners will find the book an invaluable source of insight into computer ethics and law, network security, and computer crime investigation.